Spetzler-Martin Grade III Arteriovenous Malformations: A Comparison of Modified and Supplemented Spetzler-Martin Grading Systems. Issue 6 (13th February 2021) - Frisoli, Fabio A; Catapano, Joshua S; Farhadi, Dara S; Cadigan, Megan S; Nguyen, Candice L; Labib, Mohamed A; Srinivasan, Visish M; Lawton, Michael T
Abstract: BACKGROUND: The modified Spetzler-Martin (SM) grading system proposes that grade III arteriovenous malformation (AVM) subtypes are associated with variable microsurgical risks, with small AVMs (III−) having lower risk and medium/eloquent AVMs (III+) having higher risk. Adding patient age and AVM bleeding status and compactness to the SM grade produces a score – the supplemented SM (Supp-SM) grade – to more accurately assess preoperative risk. OBJECTIVE: To compare the predictive power of the modified SM and Supp-SM grades for risk assessment in patients with grade III AVMs. METHODS: Patients with SM grade III AVMs treated between 2011 and 2018 were retrospectively reviewed. Good outcomes were defined as modified Rankin Scale (mRS) scores ≤ 2 or unchanged/improved mRS scores (pre- vs postsurgery). RESULTS: Of 102 patients with SM grade III AVMs, 59% had grade III− and 24% had grade III+ AVMs. Supp SM grade 6 and grade 7 AVMs accounted for 44% and 24%, respectively. Overall, 33% of patients worsened but outcomes did not significantly differ by SM III subtype. Neurological outcomes were associated with Supp-SM grade, with proportions of patients with worsening increasing from 0% with Supp-SM grade 4 AVMs to 54% with Supp-SM grade 7 AVMs. Analyses of factors associated with neurological worsening identified age > 60 yr and Supp-SM grade 7 as significant. CONCLUSION: Supp-SM grades were more predictive of microsurgical outcomes than modified SM grades for grade III AVMs, with a hard cutoff for acceptable surgical risk at Supp-SM grade 6. Supp-SM grading is a better decision-making tool than subtyping with the modified SM scale.